Effects of resistance and all-round, functional training on quality of life, vitality and depression of older adults living in long-term care facilities: a 'randomized' controlled trial [ISRCTN87177281] - Chin A Paw, Marijke JM; van Poppel, Mireille NM; Twisk, Jos WR; van Mechelen, Willem (BMC geriatrics, 2004)
Regular physical activity may improve different aspects of wellbeing in older people, such as quality of life, vitality and depression. However, there is little experimental evidence to support this assumption. Therefore, we examined the effect of different training protocols on quality of life, vitality and depression of older adults living in long-term care facilities. Subjects (n = 173, aged 64 to 94 years, living in long-term care facilities), were randomized to six months of three different moderate-intensity group exercise training protocols, or to an 'educational' control condition. Exercise consisted of two 45-60-minute training sessions per week of 1) resistance training; 2) all-round, functional training; or 3) a combination of both. Perceived health, the Geriatric Depression Scale (GDS), the Vitality Plus Scale (VPS) and the Dementia Quality of Life questionnaire (DQoL) were administered at baseline and after six months. In the combined training group a small but significant decline was seen in perceived health, DQoL and VPS score compared to the control group. We conclude that neither strength training nor all-round, functional training of moderate intensity is effective in improving quality of life, vitality or depression of older people living in long-term care facilities.